Sensory development for heavy metal detection: A review on translation from conventional analysis to field-portable sensor. (March 2021) - Mukherjee, Subhankar; Bhattacharyya, Soumyadeb; Ghosh, Koustuv; Pal, Souvik; Halder, Arnab; Naseri, Maryam; Mohammadniaei, Mohsen; Sarkar, Subrata; Ghosh, Alokesh; Sun, Yi; Bhattacharyya, Nabarun
Abstract: Background: In recent decades, contaminations with heavy metals ions have adversely affected the environment, food safety, and human health. Heavy metals, leaching to water sources from the industrial effluents, can enter into the aquatic and food chains of humans and animals from a variety of anthropogenic sources. Scope and Approach: Heavy metal detection has been an intensive area of research today. Both laboratory-based analytical instruments and innovative sensor devices like the electronic nose, electronic tongue, and bio/chemical sensors have increasingly emerged to meet the demand for legislative actions on environmental pollution control and early warning. These evolving technology and developments particularly in the area of nanotechnology and sensors have become key contributing factors in heavy metal detection. Key Findings and Conclusions: This endeavor aims at exploring this field in detail to understand the key principles behind this flourishing science and summarize the recent development in heavy metal detection technologies. This article also gives a brief review of commercially available portable devices that has the potential to become the next gold standard instruments in heavy metal detection. Graphical abstract: Image 1 Highlights: Heavy metal contamination in water has caused a global threat to the environment, food safety and human health. The conventional techniques are sensitive, but lack of portability and rapidness. Field-portable sensors have emerged as very promising tools wherein rapid screening is a concern. This endeavor reviews translation from conventional analysis to the field-portable sensor for heavy metal detection.